A feasibility trial of acupuncture in cancer patients undergoing radiotherapy treatment. (May 2021) - Hughes, John; Gyertson, Kylie; Carballo, Lallita; Plant, Hilary; Sharman, Mitch; Ruane, Katie; Mendoza-Naranjo, Ariadna; Hackshaw, Allan; Cummings, Mike; Edwards, Alex; Lewith, George; Fisher, Peter
Abstract: Objective: We conducted a feasibility trial of acupuncture in cancer patients undergoing radiotherapy treatment. The trial included training radiographers to deliver acupuncture within patients' routine NHS care. Methods: Mixed methods pragmatic randomized parallel-group exploratory feasibility trial comparing standard care to standard care plus acupuncture. Results: Most aspects of the research design and acupuncture intervention were acceptable to the 101 participants. Participants' valued the opportunity to receive acupuncture within their NHS care, perceived the treatment as eliciting a number of beneficial effects, and had a positive impact on their NHS cancer treatment. However, quantitative analysis of outcome measure data revealed no consistent significant differences between those receiving standard care and those receiving standard care plus acupuncture. Conclusion: It is feasible to implement acupuncture in a busy radiotherapy unit provided by specially trained radiographers. The methodology employed appears acceptable for the evaluation of acupuncture for radiotherapy patients. Highlights: It is feasible to implement acupuncture in a busy radiotherapy unit provided by specially trained therapy radiographers. The methodology employed appears acceptable for the evaluation of acupuncture for radiotherapy patients. Qualitatively participants and treating radiographers found the experience positive and reported benefit. Quantitative analysis of outcome measure data revealed no consistent significant differences.